Characterization of the Bioenergy Potential of Corncob and Rice Husk mixtures in Biochar Briquettes - Asrori, Asrori; Alfarisyi, Mirza Fathus Syifa; zainuri, Ach. Muhib; Naryono, Eko (PT. ELSHAD TECHNOLOGY INDONESIA, 2024)
Briquettes are a form of solid fuel that is produced using waste from the agricultural, industrial and household sectors. For example, briquettes can be produced from biomass waste such as rice straw and corn cobs, which are potential resources that can be utilized to produce bioenergy in the form of briquettes. This study aims to develop and test the characteristics of biomass briquettes in order to evaluate the quality of the biochar briquettes and the calorific value they produce. The method used in this study was experimental, in which the adhesive and the composition of the mixed ingredients were varied as independent variables to affect the quality of the briquettes, while the moisture content, ash content, burning rate,put birds, calorific value is used as the dependent variable. In this study, the results obtained for water content ≤ 5%, volatile matter ≤ 10%, calorific value ≤ 6.553 cal/g, and a burning rate of 0.17 gram/minute which is expected according to the Indonesian National Standard (SNI) 01 6235 2000, namely the water content ≤ 8%, volatille matter ≤ 10%, calorific value ≤ 5,000 cal/g. The results of this study indicate that the biomass briquettes can meet the established quality standards, with appropriate moisture, ash and volatile matter content. In addition, the resulting calorific value also reaches the desired figure, indicating the potential of biomass briquettes as an efficient alternative fuel. The combustion rates found in this study also indicate that the biomass briquettes have characteristics that allow stable and effective combustion. Thus, this research succeeded in developing and testing the characteristics of biomass briquettes as an alternative fuel. The results of this study can contribute to the development of renewable energy sources and efficient use of biomass waste, as well as promote efforts to mitigate the negative impacts of the conventional energy sector on the environment.